7+3t-1=8t+24-2t

Simple and best practice solution for 7+3t-1=8t+24-2t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3t-1=8t+24-2t equation:


Simplifying
7 + 3t + -1 = 8t + 24 + -2t

Reorder the terms:
7 + -1 + 3t = 8t + 24 + -2t

Combine like terms: 7 + -1 = 6
6 + 3t = 8t + 24 + -2t

Reorder the terms:
6 + 3t = 24 + 8t + -2t

Combine like terms: 8t + -2t = 6t
6 + 3t = 24 + 6t

Solving
6 + 3t = 24 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
6 + 3t + -6t = 24 + 6t + -6t

Combine like terms: 3t + -6t = -3t
6 + -3t = 24 + 6t + -6t

Combine like terms: 6t + -6t = 0
6 + -3t = 24 + 0
6 + -3t = 24

Add '-6' to each side of the equation.
6 + -6 + -3t = 24 + -6

Combine like terms: 6 + -6 = 0
0 + -3t = 24 + -6
-3t = 24 + -6

Combine like terms: 24 + -6 = 18
-3t = 18

Divide each side by '-3'.
t = -6

Simplifying
t = -6

See similar equations:

| 2[4-9x]=9x+7 | | -143=3(-6b-1)+4 | | 6(5y-8)-(7y+4)= | | 9x^2+13=247 | | -4(1-5v)=-144 | | 7+5[1+2(2x+5)]=6(x+7) | | P-16=13-6p | | 4c+1-c=19 | | (x+5)(x-2)=35 | | 8b-5b-7=23 | | 8y+4y=144 | | 2.5[x+3(x+7)]= | | 6x+8y=-11 | | (3a)+(2a-25)=180 | | .50(x-2)=4x-0.2222x-4 | | 5(3b-4)=40 | | 3(4x+3)=17 | | 6r+5=4(r+2)-2r | | 2yf-3(2y-3)+2=31 | | F(x)=x^3+2x^2+x+4 | | 2n-1=-10 | | 11=4(x-1)-x | | 2600=(2x-6)m+(x+3)m | | 4x+5=16x+8-12x-3 | | 1.8x+2.8=2.5*2.1 | | -108=3(4+8n) | | 2[4x+1]+5=19 | | (8x-12)(5x-25)=0 | | (a)3.43x=5.6 | | 2[4x+1]5=19 | | 7(y-3)=4y-33 | | 25=3+9x |

Equations solver categories